Who Should Pay for Certification? - Konrad Stahl; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Who does, and who should initiate costly certification by a third party under asymmetric quality information, the buyer or the seller? Our answer ' the seller ' follows from a non-trivial analysis revealing a clear intuition. Buyer-induced certification acts as an inspection device, whence seller-induced certification acts as a signalling device. Seller-induced certification maximizes the certifier's profit and social welfare. This suggests the general principle that certification is, and should be induced by the better informed party. The results are reflected in a case study from the automotive industry, but apply also to other markets - in particular the financial market.
urn:nbn:de:bvb:19-epub-13231-2
Keywords: D40; D82; L14; L15; 330; asymmetric information; certi?cation; information acquisition; inspection; lemons; middlemen; signaling; Standardisierung; Produktqualität; Asymmetrische Information; Kunden; Kosten; Signalling; Kraftfahrzeugindustrie